Predictive value of serum uric acid levels for adverse perinatal outcomes in preeclampsia - Bhagavan, Veena; Rao, Aadhishree; Sharma, Ritu (International Journal of Reproduction, Contraception, Obstetrics and Gynecology, 2022)
Background: Hypertensive disorders of pregnancy affect 6-8% of all pregnancies and along-with haemorrhage and infection, they form a complex triad, contributing immensely to maternal morbidity and mortality. Although exact aetio-pathogenesis of pre-eclampsia is unknown, multiple factors have been implicated to have a role in it; the factors being abnormal placental implantation, endothelial dysfunction, maternal immunological tolerance, cardiovascular, genetic, nutritional and environmental factors. Increased uric acid concentration is one of the most pronounced clinical findings in preeclampsia. Hyperuricemia in preeclamptic women is primarily due to a reduction in glomerular filtration rate due to endothelial dysfunction. In this study we look to explore the relationship between elevated serum uric acid and the perinatal outcomes, especially the ability to predict adverse perinatal outcomes. Methods: This was a hospital based retrospective study, conducted in A J institute of medical sciences and research centre, from January 2020 to December 2020. 75 study participants >20 weeks with diagnosed preeclampsia were chosen and their perinatal outcomes were measured. Chi square test and Fisher exact test was used to calculate p>0.05 was considered statistically significant. Results: Mean gestational age at delivery for elevated serum uric acid was 36.8 with SD=2.57 and those with normal uric acid levels is 38.43 with SD=0.89. FGR was seen in 5 patients, among which 4 (80%) had increased serum uric acid levels and 1 (20%) had normal serum uric acid levels. Total number of neonates who had APGAR score <7 was 3, among whom 2 neonates (66.66%) were born to increased uric acid level mothers. Out of 74 neonates, total number of neonates who had NICU admission were 20, among whom 9 neonates (45%) were born to mothers with increased serum uric acid levels. Conclusions: The study concluded that elevated serum uric acid is significantly associated with adverse perinatal outcomes, like FGR, low birthweight, low APGAR score and increased NICU admissions, there was no significant association between elevated serum uric acid level and mode of delivery.